2015
DOI: 10.1007/s10803-015-2563-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Transition-Age Youth with Autism or Intellectual Disability

Abstract: We examined the subjective health and well-being of 389 transition-age youth with autism or intellectual disability using the parent proxy version of the KIDSCREEN-27. Parents reported well-being of youth with autism and youth with intellectual disability lower than a normative sample in the domains of Physical Well-being, Psychological Well-being, and Social Support and Peers. For both groups of young people, the lowest ratings were reported in Social Support and Peers. Higher ratings of well-being in one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 45 publications
5
69
1
11
Order By: Relevance
“…The results of previous studies indicated that there was a positive correlation of intellectual and cognitive abilities with optimism (Klaczynski & Fauth, 1996;Nonis & Wright, 2003) and self-efficacy (Chamorro Premuzic et al, 2010;Paunonen & Hong, 2010) in TD adolescents. The obtained findings are in accordance with the results of other comparative studies which confirmed that persons with ID were less optimistic (Biggs & Carter, 2016) and felt significantly less self-efficacious than their non-disabled peers (Forte et al, 2011). Zigler and associates (1999) reported that persons with ID were more dependent on adults, that their expectations of success in solving tasks were low, and that they were less interested in new situations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of previous studies indicated that there was a positive correlation of intellectual and cognitive abilities with optimism (Klaczynski & Fauth, 1996;Nonis & Wright, 2003) and self-efficacy (Chamorro Premuzic et al, 2010;Paunonen & Hong, 2010) in TD adolescents. The obtained findings are in accordance with the results of other comparative studies which confirmed that persons with ID were less optimistic (Biggs & Carter, 2016) and felt significantly less self-efficacious than their non-disabled peers (Forte et al, 2011). Zigler and associates (1999) reported that persons with ID were more dependent on adults, that their expectations of success in solving tasks were low, and that they were less interested in new situations.…”
Section: Discussionsupporting
confidence: 89%
“…Studies conducted on samples of adolescents with ID revealed that positive individual characteristics (e.g. optimism, self-efficacy) were a good predictor of higher quality of life (Biggs & Carter, 2016) and life satisfaction (Shogren et al, 2006).…”
Section: Intellectual Abilities and Resiliencymentioning
confidence: 99%
“…64% of parents of children with intellectual disabilities and high support needs in their early twenties described their child as having ‘a great deal’ or ‘much’ life satisfaction (Davies & Beamish ). However, parent reports of well‐being were significantly lower for young people with autism or intellectual disabilities than for a normative sample across the domains of physical well‐being, psychological well‐being and social support (Biggs & Carter ).…”
Section: Resultsmentioning
confidence: 97%
“…Clark et al 2015; Egilson et al 2016; Hong et al 2016; Ikeda et al 2014) this is not always the case (Jonsson et al 2016). Moreover, findings on the associations between QoL and factors such as autism severity, age, gender, cognitive, social and language skills, adaptive behaviours, behavioural disturbance, physical health, and co-morbid psychiatric conditions are variable, and sometimes contradictory (Biggs and Carter 2016; Chiang and Wineman 2014; Hong et al 2016; Ikeda et al 2014; Kamio et al 2013; Van Heijst and Geurts 2015). Suggestions that support networks may have a stronger impact on QoL in autism than individual characteristics (Renty and Roeyers 2006) have also led to exploration of a wide range of potential environmental influences.…”
Section: Introductionmentioning
confidence: 99%